1992
DOI: 10.1016/0014-5793(92)80311-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcription mapping of the Ori L region reveals novel precursors of mature RNA species and antisense RNAs in rat mitochondrial genome

Abstract: We have identified new transcripts in the region surrounding the L-strand replication origin (Ori L) of rat liver mitoehondrial DNA. In particular. we have detected previously unidentified intermediates of RNA processing on both the heavy and the light strands, such as precursors ol'the ND2 mRNA plus the Trp-tRNA and precursors of the tRNAs clustered in the Ori L region. This indicates that the mechanism of RNA processing in mitoehondria proceeds step-wise producing a variety of precursors of the instate forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
(1 reference statement)
3
16
0
2
Order By: Relevance
“…It is noteworthy that the 3.6-kb ND5 ϩ Cyt-b precursor was the mitochondrial mRNA most affected by hypoxia. Stable polyadenylated mitochondrial mRNA molecules that are precursors of the mature species have been found before (57,58). Our results thus strengthen the concept that stepwise processing of the polycistronic transcripts is an additional regulatory element in the expression of the mitochondrial genome.…”
Section: Discussionsupporting
confidence: 83%
“…It is noteworthy that the 3.6-kb ND5 ϩ Cyt-b precursor was the mitochondrial mRNA most affected by hypoxia. Stable polyadenylated mitochondrial mRNA molecules that are precursors of the mature species have been found before (57,58). Our results thus strengthen the concept that stepwise processing of the polycistronic transcripts is an additional regulatory element in the expression of the mitochondrial genome.…”
Section: Discussionsupporting
confidence: 83%
“…In this process, the order of the cleavage events may play a determining role. In vitro tRNA processing experiments (36) and in vivo observations (12,37) have indicated that the order of 5Ј-and 3Ј-end cleavages of the tRNA precursors in human mitochondria may vary depending on the tRNA. Other in vitro processing experiments utilizing partially purified mitochondrial RNase P from HeLa cells have shown that a tRNA Ser(UCN) precursor carrying a 3Ј-terminal CCA is accurately cleaved by the enzyme at the 5Ј end of the tRNA (32a).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of nontranscribed regulatory regions is not surprising in mtDNA. In mammals, both the noncoding regulatory regions, that is, the large D-loop containing region and the small L-strand replication origin, have been detected among the transcribed sequences as sense and antisense RNAs, and such transcripts are probably implicated in the regulation of mtDNA replication and expression (Sbisa et al 1990(Sbisa et al , 1992.…”
Section: Transcript Mapping Of Ascidian Mtdna With Est Datamentioning
confidence: 99%